Generation Technology from Various Types of Biomass, Case Study of Forestry Waste Technology: Sawdust, Wood Chips - Akbar, Amany Zhafira; Nugroho Adi Sasongko; Donny Yoesgiantoro (International Journal of Technology and Education Research, 2026)
The global energy crisis and increasing demand for low-carbon energy sources have positioned biomass as a strategic alternative in the transition to renewable energy. Forestry waste such as sawdust and wood chips have great potential to be converted into energy, but their utilization in Indonesia is still not optimal despite their abundant availability. Indonesia produces approximately 146.7 million tons of biomass per year with an estimated energy potential of 470 GJ/year, indicating significant opportunities for energy diversification. This article examines the potential of forestry waste biomass as an energy source, developments in conversion technology, and economic and sustainability challenges. A comparative analysis of the Fujino & Hashimoto (2023) study shows that biomass can provide local economic benefits, but its effectiveness in reducing emissions still depends on supporting technology and policies. The results of the study emphasize the need to develop high-efficiency biomass generation technology and a regulatory framework that encourages the sustainable use of waste so that biomass can play a role as a pillar of national renewable energy.